Brandeis Beyond Progressivism - Strum, Philippa (University Press of Kansas, 1993)
Choice Outstanding TitleRevered as the "People's Attorney," Louis D. Brandeis concluded a distinguished career by serving as an associate justice (19161939) of the U.S. Supreme Court. Philippa Strum argues that Brandeis-long recognized as a brilliant legal thinker and defender of traditional civil liberties-was also an important political theorist whose thought has become particularly relevant to the present moment in American politics.Brandeis, Strum shows, was appalled by the suffering and waste of human potential brought on by industrialization, poverty, and a government increasingly out of touch with its citizens. In response, he developed a unique vision of a "worker's democracy" based on an economically independent and welleducated citizenry actively engaged in defining its own political destiny. She also demonstrates that, while Brandeis's thinking formed the basis of Woodrow Wilson's "New Freedom," it went well beyond Wilsonian Progressivism in its call for smaller governmental and economic units such as workerowned businesses and consumer cooperatives.Brandeis's political thought, Strum suggests, is especially relevant to current debates over how large a role government should play in resolving everything from unemployment and homelessness to the crisis in health care. One of the few justices to support Roosevelt's New Deal policies in the 1930s, he nevertheless consistently criticized concentrated power in government (and in corporations). He agreed that the government should provide its citizens with some sort of "safety net," but at the same time should empower people to find private solutions to their needs.A half century later, Brandeis's political thought has much to offer anyone engaged in the current debates pitting individualists against communitarians and rights advocates against social welfare critics.